Utilisation of solar cell energy as physics learning media - Nur Azizah Lubis; Siti Khairunnisa; Mentari Darma Putri (Universitas Sultan Ageng Tirtayasa, 2023)
Electrical energy is one of the human needs that is often used in everyday life. However, the power plant used is still conventionally using fossil fuels, gas oil or coal which is getting depleted, while the need for electricity is increasing. The benefits of how solar cells work as a learning medium is one of the studies as an example of the utilisation of solar thermal energy into electrical energy.This research uses experimental methods. The results of the efficiency of the benefits of how the solar cell works as a learning media feasibility percentage of 75.6% From the results of panel test data for 5 times observed periodically produced an efficiency of 83% at the time of use 30 minutes, 85% at the time of use 60 minutes, 79% at the time of use 90 minutes, 68% at the time of use 120 minutes and 63% at the time of use for 150 minutes. So that the total efficiency done by solar panels can be 75.6% and the tools used as solar cell media can work properly. Voltage, current, electric power and efficiency of the lamp produced are influenced by the size of the temperature of the solar heat, if the temperature of the solar heat is high then the resulting efficiency increases and vice versa. If the sunlight is low then the value of efficiency, current, voltage and power will decrease.